2010
DOI: 10.1007/s00117-010-2071-0
|View full text |Cite
|
Sign up to set email alerts
|

Prävalenz und klinische Bedeutung inzidenteller Herzbefunde im nicht EKG-getriggerten Thorax-CT

Abstract: Incidental cardiac findings are frequent in non-ECG-gated chest CT and may have a high clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[ 18 ] Other studies showed similar results. [ 20 , 21 ] The authors reasoned that the radiologist concentrate on the lungs and not on the heart. Regarding nonreported CRCIFs in our study, there are several reasons to be recognized.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Other studies showed similar results. [ 20 , 21 ] The authors reasoned that the radiologist concentrate on the lungs and not on the heart. Regarding nonreported CRCIFs in our study, there are several reasons to be recognized.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between non-caseous and caseous can be best appreciated on “bone window” setting which in the case of caseous MAC reveals a shell of calcification and an area of central homogenous hyperattenuation. [ 8 10 ] Caseous and non-caseous MAC can also be distinguished on magnetic resonance imaging, in which caseous MAC gives a high T1 signal and a low T2 signal on noncontrast sequences and a unique peripheral enhancement of the mass with late gadolinium enhancement. Non-caseous MAC gives a low T1 signal.…”
Section: Discussionmentioning
confidence: 99%